Contribution of Dysregulated B-Cells and IgE Antibody Responses to Multiple Sclerosis - Seals, Malik R.; Moran, Monica M.; Leavenworth, Jonathan D.; Leavenworth, Jianmei W. (Frontiers in Immunology, 2022)
Multiple sclerosis (MS), a debilitating autoimmune inflammatory disease that affects the brain and spinal cord, causes demyelination of neurons, axonal damage, and neurodegeneration. MS and the murine experimental autoimmune encephalomyelitis (EAE) model have been viewed mainly as T-cell-mediated diseases. Emerging data have suggested the contribution of B-cells and autoantibodies to the disease progression. However, the underlying mechanisms by which dysregulated B-cells and antibody response promote MS and EAE remain largely unclear. Here, we provide an updated review of this specific subject by including B-cell biology and the role of B-cells in triggering autoimmune neuroinflammation with a focus on the regulation of antibody-producing B-cells. We will then discuss the role of a specific type of antibody, IgE, as it relates to the potential regulation of microglia and macrophage activation, autoimmunity and MS/EAE development. This knowledge can be utilized to develop new and effective therapeutic approaches to MS, which fits the scope of the Research Topic “Immune Mechanism in White Matter Lesions: Clinical and Pathophysiological Implications”.